Source of the dramatic expression. (Journal of Parents and Teachers, 2013)
Several lessons in the classroom are presented in this article in order to promote creativity with pupils in the last two years of primary and the first two years of secondary education through dramatic expression. We should mark up the importance of body control to develop all kind of abilities.
Keywords: Body expression; creativity; primary education; secondary education; didactics; activities; education.